2015
DOI: 10.1007/s13233-015-3071-8
|View full text |Cite
|
Sign up to set email alerts
|

A Shish-kebab superstructure in low-crystallinity elastomer nanocomposites: Morphology regulation and load-transfer

Abstract: In this paper, a regulated morphology of multi-walled carbon nanotube bundles (CNTBs) in olefin block copolymer (OBC) is achieved via a facile method of short-time strong sonication and solution blending. Inside the CNTBs which consist of several to dozens of nanotubes, the nanotubes exhibit a well aligned structure. With the incorporation of CNTBs, a hybrid shish-kebab superstructure is formed that nanotubes in CNTBs form the central stems and OBC crystals form kebabs on the surface of nanotubes. Superior rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Ochoa observed that the addition of cellulose nanofibers (CNFs) can increase the final crystallinity of polyethylene‐b‐polyethylene glycol (PE‐b‐PEG) diblock copolymers . Moreover, a nanohybrid shish‐kebab (NHSK) structure, which consists of central nanofiller (shish) and surrounding lamellar crystals (kebabs), has been observed in olefin block copolymers incorporating one‐dimensional nanofillers . Similar structure has also been found in PE‐b‐PEG block copolymers containing carbon nanotubes (CNTs) .…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Ochoa observed that the addition of cellulose nanofibers (CNFs) can increase the final crystallinity of polyethylene‐b‐polyethylene glycol (PE‐b‐PEG) diblock copolymers . Moreover, a nanohybrid shish‐kebab (NHSK) structure, which consists of central nanofiller (shish) and surrounding lamellar crystals (kebabs), has been observed in olefin block copolymers incorporating one‐dimensional nanofillers . Similar structure has also been found in PE‐b‐PEG block copolymers containing carbon nanotubes (CNTs) .…”
Section: Introductionmentioning
confidence: 74%
“…In the system without the repulsive interaction ( B 2 = 0), a central nanofiller periodically decorated with disk‐shaped lamellae, which is similar with the reported NHSK structure, can be observed. In experiments, such a structure has also been induced by different one‐dimensional nanofiller in diblock copolymer solutions . For instance, it has been reported that a small amount of nanofiller in the olefin diblock copolymer solution is sufficient to induce heterogeneous crystallization of the block copolymer, ultimately forming a typical NHSK structure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owning to these nanocrystalline hard domains, OBCs exhibit high melting temperature, but still remains soft elastomeric feature, a difficult balance hard to reach for general elastomers, like metallocene‐catalyzed polyethylene elastomer. Several recent works have investigated the relationships between structure and properties of novel OBCs . However, only a few OBC blends available in the literature includes OBC/PP (polypropylene), OBC/SEBS (styene‐ethylene‐butylene‐styrene copolymer), and OBC/ethylene‐octene (EO) copolymer …”
Section: Introductionmentioning
confidence: 99%